DO/ART4 gene sequencing in sub‐Saharan cohorts and African migrants: useful data describing the diversity and spreading of rare variants. Issue 12 (21st November 2019) - Chapel‐Fernandes, Sylvie; Movia, Catherine; Jordier, François; Durousseau de Coulgeans, Cécile; Chiaroni, Jacques; Bailly, Pascal
Abstract : BACKGROUND: Due to the unavailability of immunological reagents, the Dombrock blood group is insufficiently explored in African populations and can be a source of alloimmunization. A large study including pygmoid and nonpygmoid ethnic groups from East, Central, and West continental Africa, together with African migrants like Comorians, Afro‐Caribbean from Martinique, and Maroons from French Guiana would be helpful to increase transfusion safety. STUDY DESIGN AND METHODS: Using genomic DNA extracted from blood samples collected from 336 nonpygmoid and 51 pygmoid Africans as well as 268 samples of African descent, DO coding regions were PCR‐amplified and sequenced. RESULTS: DO*A and DO*B alleles were detected in almost all groups, with a clear predominance of DO*B in every cohort tested. DO*JO and DO*HY allele frequencies reached 10% or more in several ethnic groups. DO*B‐SH‐Gln149Lys, DO*B‐Ile5Thr, and DO*DODE variants were identified both in African ethnic groups and outside Africa. Twelve novel variants were characterized on a DO*A or a DO*B background. Five of them were found in both African and migrant cohorts, the others were restricted to either within or outside Africa. No DO*DOYA, DO*DOLG, DO*DOLC, nor DO*DOMR variants were observed. A first phylogenetic tree was proposed including all variant alleles. CONCLUSION: This study across continental Africa and countries with African migrants provides a useful overview of Dombrock allele diversity and distribution. The identification of 12 new alleles underlines the importance of genotyping for Dombrock alleles, particularly to improve transfusion safety in countries hosting migrant populations of African descent.